Facile Nanopatterning of PEDOT:PSS Thin Films. Issue 5 (23rd February 2018) - ElMahmoudy, Mohammed; Charrier, Anne M.; Malliaras, George G.; Sanaur, Sébastien
Abstract: Nanopatterned conducting polymer poly(3, 4‐ethylenedioxythiophene) poly(styrene sulfonate) (PEDOT:PSS) films are obtained using a new, facile fabrication method. In this method, an epoxy supporting layer is used to facilitate the transfer of nanopatterns from a polydimethylsiloxane mold to rigid or flexible substrates. This process overcomes several limitations that are previously introduced when using other nanopatterning techniques such as nanoimprint lithography and capillary force lithography. Two sets of nanopatterned PEDOT:PSS/Gold (Au) electrodes are fabricated with different dimensions: set 1 with 87 nm linewidth, 140 nm pitch, 30 nm depth; and set 2 with 157 nm linewidth, 280 nm pitch, 26 nm depth, respectively. The electrochemical impedance of these electrodes is measured to be lower than that of flat electrodes fabricated following the same process. These findings open the way for fabricating smaller electrodes with reduced impedance. Possible applications can be in the field of biosensing, neural recordings, and interfaces, where decreasing the contact impedance plays a key role. Abstract : Nanopatterning of conducting polymers is a promising approach for realizing low impedance contacts for interfacing with biological systems. In this study, an easy and reliable approach for fabricating the nanopatterned PEDOT:PSS electrodes is introduced. Then, the electrochemical impedance of the nanopatterned electrodes versus flat electrodes is investigated. The results show a reduction in the impedance as a result of the patterning.